Verringerung von Ammoniakemissionen durch Gülleansäuerung auf dem Feld: Teilnahmebereitschaft von Landwirten an Förderprogrammen; Abating Ammonia Emissions through Slurry Acidification during Spreading: Farmers' Willingness to Participate in a Support Scheme - Insa Thiermann; Gunnar Breustedt; Uwe Latacz-Lohmann (German Journal of Agricultural Economics (GJAE), 2021)
– This article sought to determine farmers' willingness to join a hypothetical support scheme for slurry acidification during spreading. Slurry acidification is a novel technique to reduce ammonia emissions, which has been pioneered in Denmark. In an online discrete choice survey of German livestock farmers, the respondents were asked to choose between different policy schemes to promote the use of acidification techniques and an opt-out option. The support schemes were characterized by the following attributes: cost share, expected emission reduction as well as a relief from, and a tightening of, the German Fertilizer Ordinance. The relief was a waiver of the legal requirement to incorporate slurry immediately after spreading. The tightening related to the provision to account for the additional nitrogen in a farmer's fertilizer planning. The data was estimated using a mixed logit model and latent class analysis. The estimated probability of choosing a support scheme was 90% in the mixed logit estimation. All attributes were crucial for the decision to use acidification techniques during slurry spreading. Higher emission reduction increased the chances of participation in a support scheme significantly. Furthermore, the cost share offered and the exemption from the requirement to incorporate slurry immediately after spreading had a significantly positive impact on farmers' willingness to participate. By contrast, the more of the extra nitrogen contained in acidified slurry had to be accounted for in a farmer's fertilizer planning, the lower the probability of participation.
Keywords: 330; Discrete-Choice-Experiment; Ammoniak; Emissions-minderung; Mixed-Logit-Modell; Ansäuerungsverfahren; Förderprogramm